CONFLITOS TERRITORIAIS E R-EXISTÊNCIAS NO FAXINAL DOS RIBEIROS – PINHÃO/PARANÁ - CORREIA, REGINALDO DE LIMA (2015)
The process of agriculture modernization, along with the Paraná settlement policies led to a series of transformations and environmental conflicts in the countryside. In forest areas, the process of occupation, justified at times the deforestation, and left the Paraná with few remaining, many of these occupied by traditional communities that resist to the processes of deforestation and forest replacement. The remaining of Forest with Araucaria in Paraná, as a rule, are occupied by a traditional population that developed its modes of being and living in territory, through the Faxinal System, present in the first, second and third Plateau of Paraná, especially in mesoregions South Central and Southeast of the State. The Faxinal System, is an organization, productive, social, cultural and environmental that integrates of a very special way, the peoples and Forests with Araucarias, through the use of lands traditionally occupied, where are developed agroforestry and livestock activities like free animals creation (small size and large size), the vegetal extraction (yerba mate and pine nuts) and subsistence agriculture based on family labor and involve a very particular culture, characterized by economic activities, religious and the crony and solidarity ties. However, in recent years this system has undergone an intense process of transformation by modifying some of their characteristics and their singular relation between society and nature. In that sense, our research has focused attention to the Faxinal dos Ribeiros, located in the city of Pinhão, where we highlight the contemporary features and we realize other reflections, trying to identify what are the factors that constitute the mode of being in the territory, and that has given specificities to this community, this community, linked to Faxinal System, its particularity, expropriation proceedings and r-existência which have configured their territoriality, is by keeping its culture and relations with the ambiance in the context of Faxinal System. For this we use the qualitative methodology by different forms of data collection, such as participant observation, interviews, and questionnaires.